Strategi Peningkatan Ekspor Fresh Dehusked Coconut Kalimantan Barat - Ananda, Istiqomah Tri; Ariadi, Bambang Yudi; Baroh, Istis (Universitas Galuh, 2024)
Fresh dehusked coconut is one of the primary products that is often exported. Fresh dehusked coconut is a coconut that has matured completely, but at the time of husking the coir is left intact above the eye of the coconut. Today, coconut is widely utilized in both primary and manufactured forms. The many benefits and high demand for coconut attract people to develop businesses with export activities. This study was conducted to analyze the internal and external factors of the company and analyze the strategy to increase fresh dehusked coconut at PT Mas Agro Satwa. The research data analysis method is descriptive qualitative to analyze the internal and external factors of the company. SWOT analysis method with IFE, EFE, and IE matrices to analyze strategies for increasing fresh dehusked coconut at PT Mas Agro Satwa. The results showed that the internal factors seen from the number of strength scores (2.35) were greater than the number of weakness scores, namely (1.16) this shows that PT Mas Agro Satwa is able to use strengths to cover its weaknesses. External factors seen from the number of opportunity scores (2.20) greater than the number of threat scores, namely (1.55) this shows that PT Mas Agro Satwa is able to take advantage of opportunities to deal with threats that may occur. The results also show that PT Mas Agro Satwa is in quadrant I which shows that the strategic position of PT Mas Agro Satwa is in the Grow and Build position where this condition describes the company is growing and developing. The right strategic step for PT Mas Agro Satwa at this time is an intensive strategy with market penetration, product development and market development.